The Modification Mechanism of Nano-Liquids on Streamer Morphology and Breakdown Strength under Microsecond Pulse - Diangeng Li; Zicheng Zhang; Shifei Liu; Song Li (Applied Sciences, 2020)
In liquid mediums, whether the breakdown strength can be greatly improved after introducing the nano-particles has been widely investigated, however, there has been no scientific consensus on the modification mechanism of this anomalous phenomenon. In this paper, we first experimentally measured the streamer morphology and breakdown strength in pure transformer oil, TiO<semantics>2</semantics> nano-liquids and Al<semantics>2</semantics>O<semantics>3</semantics> nano-liquids under microsecond pulse. The results demonstrated that there are significant differences in streamer morphology between pure transformer oil and nano-liquids, as the streamers in pure transformer oil exhibit thick bush-like qualities, while in nano-liquids they exhibit tree-like qualities. Moreover, the breakdown voltage results show that the breakdown strength of transformer oil is improved after nano-modification, and the TiO<semantics>2</semantics> nano-liquids and Al<semantics>2</semantics>O<semantics>3</semantics> nano-liquids have nearly the same optimal volume fraction. The results of the analysis indicate that the modification mechanism of nano-particles is significantly linked to the trapped electrons process. Specifically, the addition of nano-particles can affect the electrons’ density and thus affect the breakdown process and streamer morphology.